Association of Diaphragmatic Function by Ultrasound and WIND Classification in Surgical Intensive Care Unit - Pongratananukul, Suphachok; Chittawatanarat, Kaweesak; Wannasopa, Yutthaphan; Kacha, Srisuluk; Chandacham, Kamtone (The Thai Journal of Surgery, 2023)
Background: The issue of weaning patients off mechanical ventilation remains a significant concern within the intensive care unit (ICU). Weaning, as defined by the Weaning according to a New Definition (WIND), is a valuable approach for predicting the probability of successful extubation or potential complications following mechanical ventilation. Ultrasonic diagnostics have emerged as a promising tool for evaluating various aspects of diaphragmatic function. Objective: To investigate the relationship between ultrasonic diaphragmatic parameters and the WIND classification group. Methods: This was a prospective observational study in which intubated surgical intensive care unit (SICU) patients were included. Diaphragmatic ultrasounds were performed on these patients. After the patients were discharged from the SICU, they were classified into each WIND group, and the association between the WIND group and diaphragmatic ultrasound parameters was analyzed. Results: A total of 128 mechanically ventilated patients were included in the study. The majority of patients, 90 (70%), were assigned to the WIND 1 group, while 24 (19%) were assigned to the WIND 2 group, and 8 (6%) were assigned to the WIND 3 group. Additionally, 6 (5%) patients were assigned to the WIND NW group. The median age of the patients was 67, with a range of 53 to 75. The most common type of respiratory failure experienced by the patients was peri-operative, accounting for 68% of cases. There were no significant differences observed in other baseline characteristics among the different groups. However, when examining diaphragmatic thickness at the end inspiration, a statistically significant difference was found on the right side. The WIND 3 group had the lowest measurement of diaphragmatic thickness at 1.5 mm. It is important to note that there were no significant differences in diaphragmatic thickness parameters between the groups. Conclusions: Diaphragmatic ultrasonography lacks the ability to differentiate between the various WIND groups. However, the success of weaning is different among WIND classifications.